Pattern of Recurrence After Platinum-Containing Definitive Therapy and Efficacy of Salvage Treatment for Recurrence in Patients with Squamous Cell Carcinoma of the Head and Neck - Wakasugi, Tetsuro; Nguyen, Thi Nga; Takeuchi, Shoko; Ohkubo, Jun-ichi; Suzuki, Hideaki (Frontiers in Oncology, 2022)
Background: In first-line systemic therapy for unresectable recurrent and/or metastatic squamous cell carcinoma of the head and neck (R/M SCCHN), regimens are generally selected by time-to-relapse with 6 months cutoff after platinum (Pt)-containing definitive therapy, Pt-refractory or Pt-sensitive recurrence, but clinical characteristics between Pt-refractory and -sensitive recurrence of R/M SCCHN has not fully investigated. This study aimed to evaluate pattern of recurrence and efficacy for salvage treatment for recurrence after Pt-containing definitive therapy for R/M SCCHN in a real-world setting. Methods: We retrospectively reviewed 150 patients treated with Pt-containing definitive therapy and analyzed pattern of recurrence and efficacy of salvage therapy for 63 patients with R/M SCCHN. Results: Pt-refractory recurrence, Pt-sensitive recurrence, second primary cancer (SPC), and no relapse occurred in 23.3%, 18.7%, 14.7%, and 43.3% of patients, respectively. In the cases with distant metastatic recurrence, symptomatic recurrence was significantly more common in the Pt-refractory recurrence, while asymptomatic recurrence was significantly more common in the Pt-sensitive recurrence. The timing of detection of SPC was after two years in 59.0% of cases after the completion of definitive therapy and 63.6% of SPC were asymptomatic. There was a significant difference in ΔNLR2 (NLR after definitive therapy minus NLR at detection recurrence) (p=0.028) and in prognosis after the detection of recurrence for the overall population (p=0.021), and for salvage treatment group (p=0.023), and systemic therapy group (p=0.003) between Pt-refractory and Pt-sensitive groups. Conclusions and Significance: Our analysis revealed the recurrence pattern after Pt-containing definitive therapy, and showed that the validity of dividing patients into Pt-refractory and Pt-sensitive recurrence with different prognosis in salvage therapy, especially systemic therapy.